Mapping urban heat islands in Durban (2010–2025). A longitudinal ecological remote sensing study. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2026)
Background Urban Heat Islands (UHIs) are an escalating environmental and public health concern in rapidly urbanising cities, particularly in the Global South. Durban, a major coastal city in South Africa, has undergone significant land-use and land-cover transformation over recent decades, potentially intensifying surface temperature dynamics. Understanding long-term UHI trends is essential for supporting climate-resilient urban planning, reducing heat-related risks, and promoting sustainable city development. Methods This study adopted a longitudinal ecological remote sensing design to assess UHI dynamics in Durban between 2010 and 2025. Multi-temporal Landsat and Sentinel satellite imagery were used to derive land surface temperature (LST) and classify land-cover types. Spatial analysis techniques were applied to examine temperature distribution patterns, while temporal trend analysis and correlation statistics were used to evaluate associations between LST and land-cover changes, including built-up expansion, vegetation loss, and coastal proximity. Results Findings indicate a consistent intensification of UHI patterns over the 15-year period. Mean LST in densely built-up areas increased from 28.4 °C in 2010 to 31.2 °C in 2025 (+2.8 °C), while vegetated zones recorded a smaller increase of +1.2 °C. Impervious surface expansion (approximately 20%) showed a strong positive correlation with elevated LST values (r = 0.76, p < 0.01). Inland urban zones demonstrated a statistically significant warming trend (β = 0.18 °C per year, p < 0.05), whereas areas with high vegetation cover and coastal influence exhibited cooling effects of up to 2 °C relative to industrial zones. Recommendations Urban planners and policymakers should prioritise green infrastructure development, protect and restore vegetated areas, and integrate heat mitigation strategies into land-use planning frameworks. Institutionalising remote sensing-based monitoring systems is essential to support evidence-based climate adaptation and sustainable urban management in Durban.